Development of quickscanner mobile application for grocery price checker using barcode scanner / Mohamad Hakimi Ab Rahman - Ab Rahman, Mohamad Hakimi (2017)
QuickScanner (QS) Mobile Application is basically a mobile application developed to help customer of grocery store to check the price of each products. It also can be used for budget planning. It can check the total purchases during the shopping process without the need to go to the cashier’s counters. Nowadays, almost everyone own a mobile phone. It is a must have gadget nowadays. Thus, it is necessary to take full advantage of it. Currently, many grocery store in Malaysia still using normal method to check price which is by searching for price tag. It is troublesome if the price tag is damaged or lost. There are also stores that uses in-store barcode scanner to check price. But it needed for customer to find it somewhere in the store and it usually have only a few in the store. Besides that, customer also need to bring their own calculator to check the total spending that day. As a result, a mobile application named “QuickScanner” is developed together with Software Requirement Specification (SRS) and Software Design Document (SDD). This application is mainly to cater all the stated problem. By using this application, customer can check the price of product by scanning barcode using mobile phone’s camera. It can also calculate the total price for the purchases without the need of additional device. As a conclusion, the development of QuickScanner Mobile Application can solve those problems. By having this application, users can be at ease when shopping without any worries.